Applicability of Geostatistical Tools and Fractal Theory for the Estimation of the Effect of a River on Water Relations in Adjacent Area. (14th October 2015) - Janik, G.; Olszewska, B.; Pływaczyk, L.; Łyczko, W.; Albert, M.; Nowicka, E.
Abstract: The paper presents a new method of estimation of the effect of a river on the ground waters of the adjacent area, different than the one used so far and based on the application of geostatistical methods and the fractal theories. An analysis was performed of a 14‐year series of daily observations of ordinates of water level in the river Oder and ordinates of ground water levels in five piezometers situated at various distances from the riverbed, within the range from 120 to 1000 m. The first stage of the analysis was devoted to evaluation of the applicability of classical statistical measures. It was found that only selected ones display a relation with the distance. Those included maximum value, ranges, coefficients of variation, and variances. The remaining ones proved to be non‐applicable. The next stage was the analysis of correlations between the parameters of semivariograms of ground water levels in the piezometers and the parameters of semivariograms of water levels in river Oder. It was demonstrated that the values of each parameter were related with the distance of a given piezometer from the riverbed. This means that they are useful for the estimation of the effect of the river Oder on the adjacent areas, as are the fractal dimensions. Copyright © 2015 John Wiley & Sons, Ltd.